Antifungal activity of clove (Eugenia caryophyllata) extract against Fusarium oxysporum cutinase enzyme in Tomato (Solanum lycopersicum) from in vitro study - Khairunnisa', Amalia; Syib’li, Muhammad Akhid; Abadi, Abdul Latief (Research Journal of Life Science, 2023)
Fusarium oxysporum f.sp. lycopersici presents a notable threat to tomato plants due to the hydrolytic activity of its cutinase enzyme, which facilitates the penetration of plant root tissues. Thus, reducing cutinase activity through the application of cloves as inhibitors offers an environmentally friendly alternative to hazardous chemical fungicides, showing great promise in controlling Fusarium wilt disease, particularly by targeting the cutinase enzyme of Fusarium oxysporum. This study involved GC-MS analysis of clove extract, fungal growth and cutinase activity assay using rhodamine-b olive oil media. Hence, this study aims to reveal the potential and mechanism of clove extracts as inhibitors of cutinase enzymes to reduce the penetration of the Fusarium oxysporum pathogen in tomato plants. The result shows that clove extract, containing approximately 20% antifungal compounds primarily eugenol (11% of total peak area), inhibits Fusarium oxysporum growth. It also reduces the hydrolytic activity of cutinase crucial for fungal penetration, evidenced by decreased fluorescence halos in tests with rhodamine-B and olive oil media under UV light after adding 1%, 2%, and 3% clove extract. Further in vivo studies are needed to explore its direct effects as a plant inhibitor.